MODERN FACTORS OF SOCIETY STABILITY - Avazov Komil (American Journals Publishing, 2022)
Reality gives rise to contradictory trends: the combination of new threats, tense situations and destructive trends creates awareness of the importance of identifying, assessing and managing emerging situations and the development of new scientific paradigms in addressing the threat to the sustainability of society.Public opinion is one of the core concepts of the political science system, occupying an important place in the structure of any research on political communication, political behavior, and the activities of political institutions. It is assumed that public opinion determines certain parameters of political behavior. The events of recent decades show that various political actors can take advantage of mass political movements to change power or attempt to change power outside the electoral process. Reality gives rise to contradictory trends: the combination of new external and internal threats to the state, tense situations and destructive trends creates awareness of the importance of identifying, assessing and managing emerging situations and the development of new scientific paradigms.
Keywords: Threat tolerance, societies, system, geopolitics, globalization, threat, security.